Pendampingan Packaging Dan Label Produk Makanan Pada Usaha Bumbu Oma Nusantara - Adriana Madya Marampa; Chrismesi Pagiu; Rati Pundissing (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity was carried out with the aim of improving packaging quality and providing clear information to consumers, thereby enhancing visual appeal and market value. The service was conducted at a business producing seasoning for soup noodles and fried noodles, namely Bumbu Oma Nusantara. The method used in this activity involved lectures and hands-on practice on labeling and product packaging. The result of this service activity is the creation of a seasoning product that has been packaged and labeled with a more professional appearance, making it more ready for broader marketing. Products that were previously packaged simply now have greater appeal to consumers.